Economywide impact of Avian influenza in Ghana: A dynamic computable general equilibrium (DCGE) model analysis - Diao, Xinshen (2011)
A dynamic computable general equilibrium (DCGE) model is used to quantitatively assess the economywide impact of HPAI in Ghana. The likely effect of an Avian influenza outbreak is modeled as demand or supply shocks to the poultry sector. The analysis shows that while the chicken sector is quite a small sector of the Ghanaian economy, the shock in chicken demand due to consumers’ anxieties is the dominant factor causing the fall of chicken production. The indirect effect on soybean and maize that are used as chicken feed is also large. Under the worst-case scenario, soybean production will fall by 37% and maize by 6.4%. However, the economywide impact on both agricultural gross domestic product (GDP) and GDP is very small. In the worst-case scenario, in which chicken production falls by 70% in 2011, agricultural GDP falls by only 0.47% and GDP is almost unchanged. However, the livelihood impacts of a HPAI outbreak could be significant for some sections of the population in Ghana particularly those involved in the poultry sector. Micro-level analysis of chicken producers’ livelihood, therefore, is necessary.